Pengaruh Attractiveness Terhadap Buying Decision dengan Competitive Advantage Sebagai Variabel Moderasi dalam Perspektif Manajemen Bisnis Syariah - Husni Ainurridho; Suhendar; Zathu Restie Utamie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of attractiveness on buying decisions with competitive advantage as a moderating variable in the context of sharia business management. The research was conducted on consumers of “Sahabat” beef kiosk in Pringsewu using a quantitative approach and SmartPLS analysis. The results show that attractiveness significantly influences buying decisions, and competitive advantage strengthens this effect. In sharia business, ethical attractiveness and trustworthy competitive advantage support purchase decisions with spiritual value.